Sumber Sejarah Visual: Antara Pemosisian Sumber dan Penerapan Kajian Sejarah - Pradita, Dennys; Itawan, Devi (Candrasangkala: Jurnal Pendidikan dan Sejarah, 2023)
Visual or Photographic historical sources contain potential information for historians. Moreover, it often neglected to be addressed as primary historical sources. By applying the qualitative method, this research aimed to analyze visual sources utilization in historical research. The shortfall of visual sources utilization in historical research was influenced by the prioritization of record sources and the lack of ability to analyze visual sources. Apart from being a basis for conducting historical research, visual sources can also be transformed into various print media and exhibited. The transformation of visual historical sources and exhibitions can be developed into historiography based on applied history